Theory to practice: How the City of Utrecht develops a Health and Equity in all Policies approach. (30th September 2020) - Weber, M; Droomers, M
Abstract: Introduction: We witness an increase in Health in All Policies approaches worldwide. In Utrecht this inter-sectoral and multi-level governance approach is strong since several years. Utrecht has made progress in linking spatial challenges with social challenges, aiming for healthy urban living for all. An example is social renovation, in which social housing corporations combine physical renovation with social programs in Overvecht, the most socio-economically deprived neighbourhood in Utrecht. The project addresses social determinants of health, such as income, education and employment, and subsequently improvement of health of the residents. Methods: In April 2020, social renovation of an apartment building of around 180 households will start. During the exploration phase, community workers carry out door-to-door visits. This forms the basis for community development activities and provides the possibility to refer residents directly to professional assistance. After one year, the actual renovation starts. Following, new residents are purposely selected and assigned to the newly renovated flats that have been vacated during the process. Results: Impact of the social renovation process on health and health determinants will be evaluated. The door-to-door visits are used to interview the residents about their wellbeing, stress, mental and physical health condition, sense of mastery, financial problems, perceived safety, and social and physical living environment. Interviews will be repeated during the community development phase (after six months), and just before the start of the physical renovation (after one year). Discussion: Social renovation aims to contribute to and preferably improve residents' personal living conditions and social living environment, instead of just improving their housing conditions. Lessons learned from this process will inspire replication and upscaling in other neighbourhoods.